From austerity to abundance? : creative approaches to coordinating the common good - Stout, Margaret (Critical perspectives on international public sector management, 2019)
This volume explores the ways in which civil society andgovernments employ transformative tactics of direct engagement in coordinatingefforts toward the common good. Increasingly, these collaborative endeavorsseek to share power and break down role boundaries in the pursuit of abundanthuman flourishing, as opposed to cost-saving austerity.